Characteristics of high and low achievers in high school integrated science - De Guzman, Ligaya Sison (1975)
In any school situation, there is the possibility that two kinds of students are present - the high achiever and the low achiever. The problem under consideration sought to determine some characteristics of high and low achievers in Integrated Science among the selected freshman and sophomore students of Quezon City High School, Ramon Magsaysay High School (Manila) and Victorino Mapa High School.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Underachievors